MICOS coordinates with respiratory complexes and lipids to establish mitochondrial inner membrane architecture - Friedman, Jonathan R (eLife, 2015)
The conserved MICOS complex functions as a primary determinant of mitochondrial inner membrane structure. We address the organization and functional roles of MICOS and identify two independent MICOS subcomplexes: Mic27/Mic10/Mic12, whose assembly is dependent on respiratory complexes and the mitochondrial lipid cardiolipin, and Mic60/Mic19, which assembles independent of these factors. Our data suggest that MICOS subcomplexes independently localize to cristae junctions and are connected via Mic19, which functions to regulate subcomplex distribution, and thus, potentially also cristae junction copy number. MICOS subunits have non-redundant functions as the absence of both MICOS subcomplexes results in more severe morphological and respiratory growth defects than deletion of single MICOS subunits or subcomplexes. Mitochondrial defects resulting from MICOS loss are caused by misdistribution of respiratory complexes in the inner membrane. Together, our data are consistent with a model where MICOS, mitochondrial lipids and respiratory complexes coordinately build a functional and correctly shaped mitochondrial inner membrane. DOI: http://dx.doi.org/10.7554/eLife.07739.001